Common Problems in Acute Care Surgery - Moore, Laura J.; Todd, S. Rob.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive, evidence-based review of the most common clinical problems encountered by acute care surgeons. Focusing on the clinical care of the patient, this volume explores the general principles of acute care surgery and the specific disease states that are commonly encountered by acute care surgeons. The work also touches upon the ethical issues and systems development behind acute care surgery, including practical considerations for establishing an acute care surgery program, ethical considerations in acute care surgery, and the role of palliative care. The second edition of the text include updates to all of the chapters from the first edition. New topics addressed include management of intra-abdominal infections, management of the open abdomen, and hemodynamic monitoring of the critically ill surgical patient. Each chapter addresses a specific topic in acute care surgery. All chapters are written by experts in the field of Acute Care Surgery. Each chapter includes a brief overview of the epidemiology of the clinical problem, the clinical presentation and diagnosis of the problems, and a discussion of the treatment options and potential complications that may arise. Common Problems in Acute Care Surgery, Second Edition will be of great value to surgical residents, fellows, and practicing acute care surgeons.
Section I: General Principles -- Initial Resuscitation and Management of the Hemodynamically Unstable Patient -- The Evaluation of the Acute Abdomen -- Perioperative Considerations for Surgical Emergencies -- Perioperative Management of the Cirrhotic Patient -- Surgical Procedures in the Intensive Care Unit -- Hemodynamic Monitoring in the ICU -- Early Management of Sepsis, Severe Sepsis, and Septic Shock in the Surgical Patient -- Multiple Organ Failure -- Acute Respiratory Distress Syndrome -- Nutrition in the Surgical Patient -- Renal Replacement Therapy -- Management of Surgical Site Infections -- Hemorrhage and Transfusions in the Surgical Patient -- Principles of Vascular Access -- Management of Intra-Abdominal Infections -- Obtaining a Surgical Airway -- Esophageal Perforation -- Pneumothorax, Hemothorax, and Empyema -- Acute Paraesophageal Hernia -- Peptic Ulcer Disease for the Acute Care Surgeon -- Gastric Outlet Obstruction -- Upper Gastrointestinal Bleeding -- Acute Biliary Disease -- Management of Complications from Biliary Surgery -- Liver Abscesses -- Acute Pancreatitis -- Small Bowel Obstruction -- Appendicitis -- Diverticulitis -- Mesenteric Ischemia for the Acute Care Surgeon -- Large Bowel Obstruction -- Lower Gastrointestinal Bleeding -- Volvulus -- Anorectal Disease -- Management of Complications of Endoscopic Therapy -- Complications of Morbid Obesity Surgery -- Abdominal Wall Hernias: Emergency Ventral Hernia Repair -- Damage Control Surgery and the Open Abdomen -- Abdominal Compartment Syndrome -- Necrotizing Soft Tissue Infections -- Acute Compartment Syndrome -- Palliative Care In The Acute Care Surgery Setting -- Common Ethical Problems in Acute Care Surgery -- Advance Directives -- EMTALA Review.
Keywords: Medicine; Surgery; Traumatology; Medicine & Public Health; Traumatic Surgery; General Surgery